Effects of trace elements applied to cows in transition period on serum fatty acid profile - Kizil, Ö; Kizil, M (Journal of the Hellenic Veterinary Medical Society, 2023)
The aim of this study was to determine the effects of a trace element solution applied to cows in the transition period on the levels of fatty acids in the transition period. The material of this study consisted of 20 clinically healthy 3-5 year old simental cows kept under the same care and feeding conditions. Pregnant cows used in the study were divided into 2 equal groups with 10 cows in each group. A single dose of 20 ml of a trace element solution was administered intramuscularly to the pregnant cows in the study group 3 weeks before the birth. Blood samples were taken for analysis at the time of trace element administration, the moment of birth and 3 weeks after birth. Serum samples were analyzed using gas chromatography-mass spectrophotometry (GC-MS) device. When the findings of the study were examined, the fatty acid levels determined 3 weeks before the birth in the group in which trace element solution applied were higher compared to the moment of delivery and the period 3 weeks after birth. In the control group, the fatty acid levels determined 3 weeks before the birth increased at the time of delivery, and the fatty acid levels determined 3 weeks after the birth remained higher than the levels determined 3 weeks before the birth. It was concluded that trace element supplementation applied to pregnant cows during the transition period prevented excessive increase in serum fatty acid levels during the transition period.